2010
DOI: 10.1182/blood-2008-11-188938
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-based discovery of a novel, structurally unique, and developmentally regulated plasminogen receptor, Plg-RKT, a major regulator of cell surface plasminogen activation

Abstract: Activation of plasminogen, the zymogen of the primary thrombolytic enzyme, plasmin, is markedly promoted when plasminogen is bound to cell surfaces, arming cells with the broad spectrum proteolytic activity of plasmin. In addition to its role in thrombolysis, cell surface plasmin facilitates a wide array of physiologic and pathologic processes. Carboxypeptidase B-sensitive plasminogen binding sites promote plasminogen activation on eukaryotic cells. However, no integral membrane plasminogen receptors exposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
180
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(186 citation statements)
references
References 72 publications
(78 reference statements)
5
180
1
Order By: Relevance
“…We have designated these Abs as anti-Pg-RIBS mAbs, according to the terminology of Zamarron and colleagues. 9 To further address the relationships between changes in Glu-Pg conformation and cellular binding sites, we found that Glu-Pg binding to the C-terminal peptide of the recently described Pg receptor, Plg-R KT , 18 was detected with the anti-Pg RIBS mAbs and the binding was not inhibited in the presence of soluble Glu-Pg. Therefore, binding of Glu-Pg to the C-terminus of Plg-R KT mimicked the interaction of Glu-Pg with the cell surface, with respect to conformational changes detected by the anti-Pg RIBS mAbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have designated these Abs as anti-Pg-RIBS mAbs, according to the terminology of Zamarron and colleagues. 9 To further address the relationships between changes in Glu-Pg conformation and cellular binding sites, we found that Glu-Pg binding to the C-terminal peptide of the recently described Pg receptor, Plg-R KT , 18 was detected with the anti-Pg RIBS mAbs and the binding was not inhibited in the presence of soluble Glu-Pg. Therefore, binding of Glu-Pg to the C-terminus of Plg-R KT mimicked the interaction of Glu-Pg with the cell surface, with respect to conformational changes detected by the anti-Pg RIBS mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the presence of EACA, soluble Glu-Pg exposes an epitope that is also exposed when Glu-Pg is associated with cells, consistent with binding of Glu-Pg to cellsurface proteins exposing C-terminal lysines, as exemplified by Plg-R KT . 18,38 These anti-Pg RIBS mAbs have many potential uses for future investigations of structure/function relationships in the field of plasminogen activation. For example, they could be of great use in imaging studies of cell-or fibrin-associated Pg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integral membrane protein plasminogen receptor, Plg-R KT , has been identified. 32 Plg-R KT promotes activation of plasminogen and colocalizes with urokinase-type plasminogen activator receptor (uPAR). 32,33 Urokinase-type plasminogen activator is abundant in urine and requires activation by uPAR.…”
Section: Discussionmentioning
confidence: 99%
“…32 Plg-R KT promotes activation of plasminogen and colocalizes with urokinase-type plasminogen activator receptor (uPAR). 32,33 Urokinase-type plasminogen activator is abundant in urine and requires activation by uPAR. The present data show urinary excretion of soluble uPAR at similar levels between PE patients and healthy pregnant women.…”
Section: Discussionmentioning
confidence: 99%